Measurement of CA15-3 level among women attending the surgery department at Brack General Hospital – South of Libya (Journal of Medical Sciences, 2022)
CA15-3 is one of the most widely used tumor markers for diagnosing and monitoring therapy of breast cancer. However, scientific studies have differed significantly in the importance of measuring this antigen for early diagnosis of breast cancer.The study was conducted on 72 women who visited the surgery department of the Brack general hospital, The concentration of CA15-3 was measured using enzyme-linked immunosorbent assay (ELISA).The results showed that the level of CA15-3 was elevated in 2 samples (2.77%) with  a mean level of 38.5 ± 1.7 U/ mL, and 70 samples (97.23%) was were normal with  a mean level of 13.77 ± 6.17 U/ml. The statistical analysis showed significant differences between the concentrations in the high and normal samples (P = 0.00). We conclude that CA15-3 is not a reliable test to confirm breast cancer.